Pengaruh Harga Minyak Dunia, Suku Bunga, Inflasi Dan Nilai Tukar Terhadap Harga Saham Sektor Pertambangan Pada Indeks LQ45 Periode 2011-2018 - Fitrah Auliana; Tahmat Tahmat (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2019)
The purpose of this study is to find out and analyze the influence of partial and simultaneously of external factors of the company specifically crude oil price, interest rate, inflation and exchange rate towards mining stock price. Object of this study are mining companies that listed in Indonesian Stock Exchange and entered in LQ45 indices period of 2011- 2018. Method of analysis in this research is panel data regression analysis. With purposive sampling method, 13 companies obtained that will be the object of research.Based on research results, crude oil price, interest rate, inflation and exchange rate have simultaneously effect towards mining stock prices. But in partially, just crude oil price and interest rate have effect towards mining stock prices, while inflation and exchage rate haven’t partially effect towards mining stock price in LQ45 indices period of 2011-2018.